Canada's corruption at home and abroad: An introduction to the special issue. Issue 1 (2nd January 2017) - Rotberg, Robert I.
ABSTRACT: Although Canada is widely regarded as among the least corrupt countries of the world, and so evaluated by the leading indexes, corruption still exists in today's Canada. This introduction to a special issue on the nature of corruption in Canada recalls corrupt eras in the nation's not-so-distant past and in the years of this decade. Although space prohibited articles on every aspect of Canada's lingering corruption, the special issue managed to contain new discussions of corruption among the First Nations, corruption in the armed forces, corruption in the delivery of foreign assistance, corruption overseas by Canadian corporations, and corruption in the defense industry. A final article indicates the kinds of remedies available to reduce future outbreaks of corruption in Canada.